2020
DOI: 10.1007/s10753-019-01138-3
|View full text |Cite
|
Sign up to set email alerts
|

Pioglitazone Attenuates Experimental Colitis-Associated Hyperalgesia through Improving the Intestinal Barrier Dysfunction

Abstract: Impaired intestinal mucosal integrity during colitis involves the peroxisome proliferator-activated receptor-γ (PPARγ), an important anti-inflammatory factor in intestinal mucosa homoeostasis, which is a potential target in colitis. Recurrent chronic pain is a vital pathogenetic feature of colitis. Nevertheless, potential functions of PPARγ in the colitis-associated hyperalgesia remain unclear. This study aimed to investigate biological roles of pioglitazone in relieving colitis-associated pain hypersensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 52 publications
(54 reference statements)
3
16
0
Order By: Relevance
“…It must be noted that PPARγ expression suffered no changes due to DSS treatment or to lack of AnxA1, meaning pioglitazone could bind to its target in colon tissue at similar levels for all experimental conditions. This is in accordance with other authors who also reported PPARγ levels suffer little to no variances in colon tissue throughout the development of DSS colitis ( Huang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…It must be noted that PPARγ expression suffered no changes due to DSS treatment or to lack of AnxA1, meaning pioglitazone could bind to its target in colon tissue at similar levels for all experimental conditions. This is in accordance with other authors who also reported PPARγ levels suffer little to no variances in colon tissue throughout the development of DSS colitis ( Huang et al, 2020 ).…”
Section: Discussionsupporting
confidence: 94%
“…Data here obtained corroborated other studies which already evidenced the beneficial actions of pioglitazone in murine models of colitis ( Saubermann et al, 2002 ; Takagi et al, 2002 ; Shah et al, 2007 ; Huang et al, 2020 ) and evidenced the lack of pioglitazone effects on AnxA1 −/− mice demonstrating the pivotal role of AnxA1 for pioglitazone anti-inflammatory actions. However, these data do not rule out the effects of pioglitazone and AnxA1 are independent; inflammation exerted when lacking endogenous AnxA1 could be exceedingly exacerbated, overwhelming any attempts of PPARγ-activation linked mechanisms to halt disease progression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Although claimed to be effective on diverse cell types in the gut (epithelium, T-cells, and macrophages), the most notable target cells of PPARg agonists are macrophages and dendritic cells 16 17 18 19 . Furthermore, Phase I and II clinical trials with PPARg agonists either alone 20,21 or in combination with mesalamine 22 show barrier protective effects in UC patients. Despite these insights, the biopharmaceutical industry has not been able to harness the beneficial impact of this major target within emergent therapeutic strategies largely due to a trail of withdrawals after devastating long-term side effects including heart failure, bone fracture, bladder cancer, fluid retention and weight gain 23,24 .…”
Section: Ppar α/G Dual Agonists Are Predicted To Be Effective Barriermentioning
confidence: 99%
“…It is The copyright holder for this preprint this version posted July 19, 2021. ; https://doi.org/10.1101/2021.07. 18.452807 doi: bioRxiv preprint…”
Section: Introductionmentioning
confidence: 99%